PERANCANGAN ARSITEKTUR SISKOHAT MENGGUNAKAN KERANGKA KERJA ZACHMAN - Munir, Misbachul (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2014)
Organization of the Hajj is a national duty that involves the various elements of the Ministry and other organizations. The Ministry of Religious Affairs as the leading institution in organizing the Hajj has an obligation to make every organization of the pilgrimage a success, which is measured from the pilgrimsâ level of satisfaction regarding the service given. Integrated and computerized hajj information system/Sistem informasi dan komputerisasi haji terpadu (SISKOHAT), as a provider of information technology unit at the Directorate-General of the Organization of the Hajj and Umrah, thus SISKOHAT must be able to make information technology as a key to success for organization of the hajj starting from the registration process to the process of worship in the Holy land. In the SISKOHAT year 1432 H/2011 M blueprint report, it recommends one efficiency improvement program for hajj service process which is enterprise architecture design program. Therefore, in this study a reconstruction of SISKOHAT system requirement as one of the parts from enterprise architecture will be conducted. The framework used in this research is the Zachman Framework, because it has the most comprehensive value from the viewpoint of stakeholders and abstraction, when comparing with some enterprise architecture frameworks that exist today. The result of this research is an architecture draft document that describes the current condition of SISKOHAT, based on 6 (six) main SISKOHAT business processes, which are: registration, settlement, document completion, departure, the process of worship in Saudi Arabia, and the process of repatriation.